Nacelle intake flow separation reduction at cruise conditions using active flow control - Nambiar, Vinayak Ramachandran; Pachidis, Vassilios (Elsevier, 2022)
Turbofan engine intakes are designed to provide separation-free flow at the fan face over a wide range of operating conditions. But at some off-design conditions, like at high flight speeds and high angles of attack (AoA), the aero engine intake may encounter flow separation. This boundary layer separation inside the nacelle inlet of an aircraft engine can lead to a large number of undesirable outcomes like reduction in fan efficiency, engine stall and high levels of stress on the fan blades. Active flow control is a promising solution to reduce inlet boundary layer separation and the associated fan-face flow distortion at such off-design conditions. By blowing pressurized air into the intake near the separation point, the boundary layer is energized and separation can be controlled. This study investigates the applicability of lip blowing, an active flow control technique, to control intake separation and flow distortion at the fan-face. First, intake separation was triggered in a 3D CFD model based on the NASA Common Research Model (CRM) using high AoA cases at cruise condition (Mach number 0.85, Mass flow capture ratio ∼0.7) and the features of separated flow were analyzed. Thereafter, active flow control was introduce to the intake in the form of two types of lip blowing, direct and pitched blowing. The efficacy of lip blowing at achieving separation control in an ultra high bypass ratio turbofan engine intake has been established through this study. The present paper also examines the significance of blowing parameters like the type of blowing, blowing pressure ratio, and blowing slot dimension, at different angles of attack to identify the critical control parameters. Our research successfully establishes proof of concept by demonstrating the feasibility of using lip blowing for separation control in aero-intakes, via numerical modelling. Furthermore, this study also provides crucial insights regarding the important variables to be considered for future experimental studies, and also for detailed studies covering a wider range of operating and blowing conditions.
Keywords: Ultra high bypass ratio turbofan engine; NASA Common Research Model; Reynolds-averaged Navier-Stokes (RANS); Computational fluid dynamics (CFD); ANSYS Fluent; Intake flow separation; Active flow control; Lip blowing